2017
DOI: 10.1007/s00294-017-0706-7
|View full text |Cite
|
Sign up to set email alerts
|

Diverse roles of Dpb2, the non-catalytic subunit of DNA polymerase ε

Abstract: Timely progression of living cells through the cell cycle is precisely regulated. This involves a series of phosphorylation events which are regulated by various cyclins, activated in coordination with the cell cycle progression. Phosphorylated proteins govern cell growth, division as well as duplication of the genetic material and transcriptional activation of genes involved in these processes. A subset of these tightly regulated genes, which depend on the MBF transcription factor and are mainly involved in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The interplay between the pol and exo activity may be modulated by the interaction with one of the accessory proteins that accompany polymerase during DNA replication, like interactions with β sliding clamp and ε subunit in E. coli replisome (Park et al 2018 ; Xu et al 2016 ). It was shown that mutations in a non-catalytic subunit of Pol ɛ, Dpb2, that destabilize interactions with Psf1 and Psf3 subunits in GINS complex result in increased spontaneous mutagenesis in yeast S. cerevisiae (Dmowski and Fijałkowska 2017 ; Garbacz et al 2015 ). One can speculate that mutations in the exonuclease domain that does not affect catalytic site may affect primer terminus site switching between pol and exo site, sending more often uncorrected primer back to polymerases active site or not allowing the primer terminus to reach the exo active site.…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between the pol and exo activity may be modulated by the interaction with one of the accessory proteins that accompany polymerase during DNA replication, like interactions with β sliding clamp and ε subunit in E. coli replisome (Park et al 2018 ; Xu et al 2016 ). It was shown that mutations in a non-catalytic subunit of Pol ɛ, Dpb2, that destabilize interactions with Psf1 and Psf3 subunits in GINS complex result in increased spontaneous mutagenesis in yeast S. cerevisiae (Dmowski and Fijałkowska 2017 ; Garbacz et al 2015 ). One can speculate that mutations in the exonuclease domain that does not affect catalytic site may affect primer terminus site switching between pol and exo site, sending more often uncorrected primer back to polymerases active site or not allowing the primer terminus to reach the exo active site.…”
Section: Discussionmentioning
confidence: 99%
“…The yeast Saccharomyces cerevisiae is an excellent model to isolate and study mutants that shed light on the processes that maintain genome stability ( 2 , 3 ). The Srs2 helicase has a major role in HR regulation; it is generally thought that its role is to suppress HR events at an early stage by dismantling the Rad51-presynaptic filament ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The probability of occurrence of damage to the genetic material increases during DNA replication, when the DNA has to be unpacked and exposed. The activity of the DNA polymerases may be disrupted by the presence of DNA secondary structures, bound proteins or lesions; this may lead to stalling or even collapse of replication forks ( dmowski and fijalkowska 2017 ). In response, cellular mechanisms are activated and arrest cell cycle progression, induce DNA repair, and restore replication ( kolodner et al 2002 ; lue and yu 2017 ; palou et al 2017 ).…”
mentioning
confidence: 99%